Whatever gets you through : twelve survivors on life after sexual assault - Fowles, Stacey May; Lee, Jen Sookfong; Valenti, Jessica (Greystone Books, 2019)
"Through the voices of twelve diverse writers, Whatever Gets You Through offers a powerful look at the narrative of sexual assault not covered by the headlines--the weeks, months, and years of survival and adaptation that people live through in its aftermath. With a foreword by Jessica Valenti, an extensive introduction by editors Stacey May Fowles and Jen Sookfong Lee, and contributions from acclaimed literary voices such as Alicia Elliott, Elisabeth de Mariaffi, Heather O'Neill, and Juliane Okot Bitek, the collection explores some of the many different forms that survival can take."--